Feasibility, Quality and Assessment of Interlingual Live Subtitling: A Pilot Study - Dawson, Hayley (Journal of Audiovisual Translation, 2019)
Intralingual respeaking has been widely practiced since 2001 (Romero-Fresco, 2011), however, interlingual respeaking (from one language into another) is yet to take off. As a hybrid form of subtitling and interpreting, interlingual respeaking calls upon skills used in both professions. To transform this mode of audiovisual translation (AVT) within Media Accessibility (MA), a programme must be created to train future interlingual live subtitlers (ILSers). This paper presents the results of the first ever study on interlingual live subtitling (ILS), in which 10 participants interlingually respoke three short videos using a language combination of English and Spanish. The main areas of research in this project are feasibility, quality and training. Before expanding training in this area, ILS must be deemed feasible and an effective method of assessment must be in place to determine its quality. The average accuracy rate of the study is 97.17%, with the highest accuracy rate reaching the 98% threshold with 98.33%. The initial results point to ILS as feasible providing a training programme is put in place to build upon existing task-specific skills and develop new ones to ensure interlingual live subtitles of good quality are produced.